Developing Physical Fitness Norms for Measured Physical Fitness Among Army Reserve Officer Training Unit Cadet - Kassim, Mohar; Rustam, Shahrulfadly; Othman, Norfazilawati; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this study is to develop norm for body health fitness among Army Reserve Officer Training Unit Cadet Malaysia (ROTU). Seven selected physical fitness test battery will be used to the subject to develop the norm through this study.443 respondent (N=443) which male 212 (N=212) and female 231 (N=231) will be selected to this study including ROTU unit cadet of National Defence University of Malaysia (NDUM). 2.4 km run, push up 1 minute, sit up 1 minute, standing long jump, sit and reach, speed 30 meter and height and weight will be used as a instrument for this study. The quantitative research design with quasi experiment will be use in this research as a methodology. The methods of Quasi-experimental that will be adopted is to evaluate and measure the volume of body wellness and develop the norms. The pre and post-test will be used in this quasi-experimental study. The quasi-experimental research design in this study is the information is collected through the test when the practical session. The information will be analysed using the SPSS software version 20 to calculate the mean, standard deviation, percentage and percentile for develop health wellness norm for Malaysian ROTU  unit Cadet. The effect of this research the subject can justified their level of fitness.